Kinetic and Enhancement of Biogas Production For The Purpose of Renewable Fuel Generation by Co-digestion of Cow Manure and Corn Straw in A Pilot Scale CSTR System - Jabraeil Taghinazhad; Reza Abdi; Mehrdad Adl (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
Biogas production from anaerobic co-digestion of cow manure (CM) and corn straw residue (CSR) were experimentally investigated using a completely stirred tank reactor (CSTR) under semi- continuously feeding circumstance at mesophilic (35°C±2) temperature. The pilot-scale digester with 180 L in volume was employed under experimental protocol to examine the effect of the change in organic loading rate on efficiency of biogas production and to report on its steady-state performance. An average organic loading rates of 2 and 3 kg VS. (m-3.d-1) and a hydraulic retention time (HRT) of 25 days was examined with respect to two different CM to CSR mixing ratios of 100:0 , 75:25 and 50:50, respectively. The results showed both organic loading rates at co-digestion of CM+ CSR gave better methane yields than single digestion of cow manure. The biogas production efficiency was obtained 0.242, 0.204, 0.311 0.296, 259.5 and 235 m3.(kg VS input)-1 for 2 and 3 kg VS.(m-3.d-1) at CM to CSR mixing ratios of100:0 , 75:25 and 50:50, respectively. The reactor showed stable performance with VS reduction between 55-74% during different runs. With increment of loading rate, the VS degradation and biogas yield decreased. Modified Gompertz and logistic plot equation was employed to model the methane production at different organic loading rates and substrate concentrations. The equations gave a good approximation of the maximum methane production (rm) and the methane yield potential (P) with correlation coefficient (R2) over 0.99.Article History: Received Oct 25th 2016; Received in revised form Dec 19th 2016; Accepted 2nd January 2017; Available onlineHow to Cite This Article: Taghinazhad. J., Abdi, R. and Adl, M. (2017). Kinetic and Enhancement of Biogas Production for the purpose of renewable fuel generation by Co-digestion of Cow Manure and Corn Straw in a Pilot Scale CSTR System. Int Journal of Renewable Energy Development, 6(1),37-44http://dx.doi.org/10.14710/ ijred.6.1.37-44